Magnetically Induced Low Adhesive Direction of Nano/Micropillar Arrays for Microdroplet Transport. (10th April 2018) - Lin, Yucai; Hu, Ziying; Zhang, Miaoxin; Xu, Ting; Feng, Shile; Jiang, Lei; Zheng, Yongmei
Abstract: A kind of superhydrophobic magnetic nano/micropillar array (MNA) with optimized intrinsic dynamic wetting property has characteristics of magnetically induced dynamic tilt‐angle changes, which achieves the controlling of the directional droplet transport effectively. It is revealed that MNA has a low adhesive gradient along the direction of magnetically induced tilt‐angles. A tilt‐angles of nano/micropillars in the range of 0°–59° is realized by controlling the magnetic field intensity (0–490 mT), so that a droplet (10 µL) can be transported on MNA from one pillar to the next along the tilt‐angle direction. It is proposed that the continuous changes of magnetically induced dynamic tilt‐angles on MNA induce a gradient driving force to act on the droplet, in addition to cooperation with the low adhesive direction that results from unidirectional gradient discontinuous solid–liquid–gas three phase contact lines. The finding offers insight into designing of surface materials that can be extended into microfluidics for controlling of droplet motion and others. Abstract : Magnetically induced dynamic tilt‐angle nano/micropillar arrays with low adhesive direction achieve the directional transport of microdroplets.